Notes on Early Land Plants Today. 51. Validation of Schistochilopsis hyperarctica (Scapaniaceae, Marchantiophyta) - Konstantinova, Nadezda A.; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
Lophozia hyperarctica (Schuster 1961: 967) was described from Ellesmere Island, Canadian Arctic. However, the author stated that the species occurred in very small patches and made a collection of them in a small area, but giving every small collection a separate collection number, thus making several gatherings out of them. When describing the species he used 5 differently numbered gatherings stating “these five collections extremely skimpy, coming from the same locality and to be considered the collective representing the type” thus violating ICN Art. 41.2 (McNeill et al. 2012). This mistake was overlooked when transferring the taxon to Massula hyperarctica (R.M.Schust.) Schljakov (1972: 318), Massularia hyperarctica (R.M.Schust.) Schljakov (1985: 232), Schistochilopsis hyperarctica (R.M.Schust.) Konstant. in Konstantinova & Vasiljev (1994: 125) and Lophozia grandiretis var. hyperarctica (R.M.Schust.) Damsholt (2008: 98). The species is validated here.